Public relations activity in the Republic of Kazakhstan (Eurasian Journal of Philology Science and Education, 2015)
Author in his article considers how PR activity was created in the Republic of Kazakhstan and pays attention to PR history in our country. The author explains PR activity of the Republic of Kazakhstan in educative sphere. Pauseson teaching the students of educational institutions such as Kazakh National University named after Al-Farabi, Kazakh Economical University named after T. Ryskulov, University of International Business, KIMEP under PRmajor. The author gives information on organizations, companies and agencies of the Republic of Kazakhstan, working in public relations field. Hereby familiarizes with operation of PR agency – Tayniy Sovetnik Ogilvy. As well as pauses on problems, arising in PR educative field and PR activities.
Keywords: PR; PR activities; Tayniy Sovetnik Ogilvy.